Clustering on longitudinal lifestyle trajectories and their impact on cognitive performance - Roca-Ventura, Alba; Solana-Sánchez, Javier; Cattaneo, Gabriele; Alviarez-Schulze, Vanessa; España-Irla, Goretti; Redondo-Camós, María; Delgado-Gallén, Selma; Romero, Ruben; Buloz-Osorio, Edgar; Pascual-Leone, Álvaro; Bartrés-Faz, David (Frontiers in Psychology, 2025)
IntroductionLifestyle factors have demonstrated a significant contribution to resilience against cognitive decline and age-related diseases. However, the understanding of how combinations of modifiable lifestyle behaviors relate to cognitive trajectories across the lifespan remains limited. This study aims to explore the relationship between lifestyle trajectories—including cognitive activity, physical exercise, sleep, socialization, nutrition, alcohol consumption, tobacco use, and body mass index (BMI)—and cognitive performance in healthy middle-aged adults.MethodsData were obtained from the Barcelona Brain Health Initiative (BBHI), an ongoing longitudinal prospective cohort study. Participants completed repeated self-reports on lifestyle factors and underwent in-person neuropsychological assessments. Kml3d clustering was applied to the longitudinal lifestyle data to identify distinct profiles. Cognitive performance was then analyzed across these lifestyle clusters to evaluate associations between lifestyle patterns and cognitive status.ResultsThe results revealed that adherence to healthy lifestyle patterns was strongly associated with better cognitive performance. Specifically, individuals following profiles characterized by higher engagement in cognitive and physical activities, healthier nutrition, better psychological health, and stronger socialization showed superior cognitive status. Moreover, the findings underscored that adhering to a higher number of healthy behaviors had a cumulative positive impact on cognition. Across the studied period—spanning middle age to older adulthood—cognitive trajectories were generally stable.DiscussionThis study highlights that k-means clustering of longitudinal lifestyle data can successfully identify meaningful lifestyle profiles associated with cognitive status in middle-aged adults. The results suggest that specific combinations of modifiable lifestyle factors may exert a more pronounced influence on maintaining cognitive health. These findings provide promising insights for the development and personalization of lifestyle interventions aimed at enhancing brain health and resilience to cognitive decline.